Novel characters : a genealogy - DiBattista, Maria, 1947- (Chichester ; Malden, MA : Wiley-Blackwell, 2010)
"Novel Characters offers a fascinating and in-depth history of the novelistic character from the "birth of the novel" in Don Quixote, through the great canonical works of the nineteenth and twentieth centuries, to the most influential international novels of the present day. An original study which offers a unique approach to thinking about and discussing characterMakes extensive reference to both traditional and more recent and specialized academic studies of the novel. Provides a critical vocabulary for understanding how the novelistic conception of character has changed over time. Examines a broad range of novels, cultures, and periods. Promotes discussion of how different cultures and times think about human identity, and how the concept of what a character is has changed over time"--
"What makes novelistic characters unique? How do novelistic characters reflect or prefigure different ideas of human possibilities? Why and how has the concept of novelistic character changed over time? These are some the questions addressed in Novel Characters, an ambitious work that aims to reinstate character to its proper and central place in the art of fiction. Novel Characters argues that the novel is the literary form best suited to create characters of real, often troubling distinction, and that indeed it has a generic disposition, amounting to an obligation, to do so. DiBattista proposes a way of understanding what is distinctive about novelistic character as well as offering a discussion of how different cultures and times think about human identity. Novel Characters ranges from the "birth of the novel" in Don Quixote through the works of the nineteenth and twentieth centuries and concludes by considering today's most influential international fiction. It simultaneously develops a lexicon of terms to describe the 'development' and trace the moral genealogy of novelistic characters through various literary periods"--
Includes bibliographical references and index.
Keywords: Fiction -- History and criticism; Characters and characteristics in literature